NORMOTHERMIC EXTRACORPORAL PERFUSION IN SITU AS A WAY OF RECOVERY KIDNEY TRANSPLANTS FROM DONORS WITH SUDDEN IRREVERSIBLE CARDIAC ARREST - S. F. Bagnenko; A. E. Skvortsov; V. N. Poptsov; I. V. Loginov; A. N. Ananyev; O. N. Reznik; Y. G. Moysyuk (Вестник трансплантологии и искусственных органов)
The potential of donors after cardiac death is actual issue. The crucial point in uncontrolled donors after cardiac death is the warm ischemical time. Definition of the limit of warm ischemic time is was the one task of our work and other one is development of preservation protocol saving quality of kidneys. There were 6 uncontrolled donors with warm ischemic time from 45 up to 91 minutes in which was adapted extracorporal perfusion device for preservation and restoration of kidneys after ischemical damage. The main attention was paid to the elimination of leucocytes as the main damaging factor from modificated donor’s blood circulating in device. In 6 of such kidneys recipients from 12 were immediately graft function, and to the end of third month the average creatinine was 121,3 ± 28,9 mmol/l. Treatment of ischemically damaged kidneys by normothermic extracorporal perfusion with leucocytes depletion before procurement could consider as challenging protocol and demands further study.